O papel do professor-mediador e das práticas de leitura na formação do leitor literário - Domingues, Teresa Cristina Aliperti França (2015)
Starting from the importance of the formation of literary reader, this study aims to discuss the literary text reading practices in the classroom in the elementary school and the role of the teacher - mediator in this process. Initially we established the dialogue between the practices that I have developed in the classroom and those proposed by the Reading and Writing Program from the Government of the State of São Paulo, in order to highlight the concepts that underlie these two practices. Later, the role of the teacher- mediator is analyzed in the process of the formation of the literary reader and suggested proposals are identified which can be developed in the process. To theoretically support the research, we turn to authors such as Candido, Freire, Petit, Barthes, Smith, Perrone-Moisés, Calvino, Dios, Bajour and Castrillón, who guided our reflection. The thesis is organized into three chapters: "Reading and literary text: the reader's formation", which addresses the conceptions of reading, literature, literary text, literary literacy and literary reader, concepts which are also present at Reading and Writing Program of the Government of the State of Sao Paulo, "Literary text reading practices in the classroom: dialogues with the Reading and Writing Program", in which we present the practices of reading proposed by the program that dialogue with my own practices developed in the classroom, and " The mediator role in the formation of the literary reader", which discusses his/hers decisive role in the formation of the literary reader and suggests literary text reading practice in the classroom. It also discusses how the teacher needs to understand that the work begins with the written text, but it is essential to go beyond it, that is, give voice to the student, to turn him/her into an author, not only of a written text, but based on his/her own history, giving opportunity to him/her to be autonomous, reflect, develop critical thinking and become an effective citizen